A Comparison of Sales Taxes - Ira N. Gang; Arindam Das-Gupta (Rutgers University, Department of Economics, 1997)
We describe the simple analytics of the four main types of sales taxes under revenue neutrality: the retail sales tax, the value added tax, a cascading sales tax and a manufacturers' sales tax. The retail sales tax is shown to be equivalent to a value added tax. In order to produce equal revenues these two taxes must be at a higher rate than a cascading tax. However, output under a retail sales tax exceeds that under a cascading sales tax and deadweight losses are lower. The manufacturers' sales tax offers the worst of all worlds: with revenue neutrality the manufacturers' sales tax has a higher tax rate, lower output and greater deadweight loss than all the other taxes.
Keywords: H2; H21; H25; 330; deadweight loss; efficiency; retail; sales tax; VAT